2013
DOI: 10.4999/uhod.11070
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Predictive Value of Expression of P-AKT in Patients with FIGO IIB Locally Advanced Cervical Cancer under Chemotherapy.

Abstract: To evaluate the relation between expression of P-Akt and radiotherapy response, disease-free survival and overall survival in cervical cancer patients. A total of 50 patients with FIGO stage IIB locally advanced squamous cell cervical cancer treated primarily with chemoradiotherapy were included in the present study. All patients received external beam radiotherapy (EBRT; 46-50.4 Gy with 1.8-2 Gy of daily fraction, five times a week) followed by high-dose rate brachytherapy (HDR 26 Gy at point A, with 6.5 Gy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Other studies have analyzed pre-treatment tissues of patients with locally advanced cervical cancer and found that 86% (Kocak et al 2013), and 74% (Kim et al 2006), classify as "positive" for Akt. These studies used a different method to analyze the expression of Akt, which classified according to the intensity and quality of staining from Akt inside the cancer cell (Kim et al 2006;Suzuki et al 2010).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies have analyzed pre-treatment tissues of patients with locally advanced cervical cancer and found that 86% (Kocak et al 2013), and 74% (Kim et al 2006), classify as "positive" for Akt. These studies used a different method to analyze the expression of Akt, which classified according to the intensity and quality of staining from Akt inside the cancer cell (Kim et al 2006;Suzuki et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies report a positive correlation between Akt expression and prognosis/response, while others have found a negative correlation. In the majority of studies, the expression of Akt is observed qualitatively using immunohistochemistry method (Kim et al 2006;Faried et al 2006;Zhang & Zhang 2008;Kocak et al 2013). The aim of the present research was to detect and evaluate any relationship between the expression of Akt in cervical cancer tissues measured by the IRS (Immno Reactive Score) method and p53 index with cervical cancer chemoradiotherapy response.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation